Study of Pulley Diameter Effect on Product Quality of Grain’s Chip Molder - Alex Candra Pardede; Saipul Bahri Daulay; Lukman Adlin Harahap (Universitas Sumatera Utara, 2015)
The pulley diameter of grain’s chip molder is needed to care. The pulley diameter will affect product quality. Pulley diameter were tested to know the quality of grain’s chip produced. Research had been conducted at agricultural engineering laboratory, Agricultural faculty USU in April –August 2014 using factorial randomized block design with one factor i.e 2,5, 3,5, and 4,5 inch. Parameters observed were organoleptic test (color), yield, process capacity, uniformity of the thickness and parcentage of damage product. The results showed that the pulley diameter had no effect on the organoleptic test (color), yield and uniformity of the thickness; had significant effect on process capacity and had highly significant on parcentage of damage product. Keywords: Grain’s chip molder, pulley diameter test, product quality.